Land cover changes, biomass loss, and predictive causes of massive dieback of a mangrove plantation in Lampung, Sumatra - Budiadi, Budiadi; Pertiwiningrum, Ambar; Lestari, Lina Dwi; Jihad, Aqmal Nur; Marpaung, Boy Andreas; Prasetyo, Sigit (Frontiers in Forests and Global Change, 2023)
A new massive dieback case of Avicennia marina was observed in the area of the Sunda Strait, which started in 2020, and the cause is still unknown. This research was conducted to report the rate of mangrove degradation, measure ecological loss, and predict the causes of the dieback. Sequential imagery analysis (2019-2022) was conducted to interpret the area changes. While field data were collected before and during the dieback event (2020 and 2021) in seven research stations, representing; live mangroves, partial dieback, and full dieback sites. In addition to a literature study on the predicted cause of the dieback. Analysis of satellite imagery was conducted using the plant senescence reflectance index (PSRI) and normalized difference vegetation index (NDVI) using a research area of 200 ha from the total 528.69 ha mangrove. Ecological loss was measured as standing stock volume (SSV) and total biomass carbon (TBC). Based on the results, the mangrove dieback caused a rapid and significant loss of healthy stands (results of the PSRI) and very high density stands (results of the NDVI). The rate of healthy stand loss was 13.43 ha month-1 (during July–October 2020) and that of very high density stand loss was 14.99 ha month-1 (October 2020–April 2021), which affected 126.62 ha or 24% of the total area (last measurement in January 2022). The SSV before dieback was 118.70 (±46.1) m3 ha-1, but within 14 months, it decreased to 20.8 (±6.0), 79.80 (±52.3), and only 1.0 (±1.0) m3 ha-1 for the three different stand categories, namely, live, partial dieback, and full dieback stands, respectively. The TBC before dieback was 51.6 (±24.4) Mg C ha-1, but within the same period, it changed to 30.70 (±3.80), 69.50 (±14.6), and 51.60 (±9.4) Mg C ha-1 for live, partial dieback, and full dieback stands, respectively. Based on the literature study and field observation, we assume that the dieback was related with nitrogen enrichment, an over-supply of N from fishpond wastes surrounding the area, in addition to less flushing by the decrease of rainfall intensity in recent years. Sustainable silvofishery may be introduced to ameliorate water and soil quality.